2016
DOI: 10.4102/sajip.v42i1.1323
|View full text |Cite
|
Sign up to set email alerts
|

The psychological well-being manifesting among master’s students in Industrial and Organisational Psychology

Abstract: Orientation: Psychological well-being among master’s students is seen as a contributing factor towards having a meaningful, enjoyable and productive experience as a student.Research purpose: The purpose of this study was to provide a qualitative description of the psychological well-being experiences of first-year students in a part-time coursework master’s degree in Industrial and Organisational Psychology (IOP) in order to foster an empathetic understanding of their experiences.Motivation for the study: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Firstly, all participants in this study were first-year master students . Master students are more autonomous, agile, and resourceful than their undergraduate peers (Cilliers and Flotman 2016 ; El-Ghoroury et al 2012 ). Master students have pre-established (functional) social support networks within the university and know how/when to access the necessary social resources required to perform academically (Cilliers and Flotman 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, all participants in this study were first-year master students . Master students are more autonomous, agile, and resourceful than their undergraduate peers (Cilliers and Flotman 2016 ; El-Ghoroury et al 2012 ). Master students have pre-established (functional) social support networks within the university and know how/when to access the necessary social resources required to perform academically (Cilliers and Flotman 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Master students are more autonomous, agile, and resourceful than their undergraduate peers (Cilliers and Flotman 2016 ; El-Ghoroury et al 2012 ). Master students have pre-established (functional) social support networks within the university and know how/when to access the necessary social resources required to perform academically (Cilliers and Flotman 2016 ). These students are also known to present with higher levels of academic self-efficacy and may have crystalised coping mechanisms to manage both study-related- and environmental demands (Jorgensen et al 2016 ; Nor and Smith 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Frequencies were compared across the 3-year research period. Categorization and coding led to elaboration and interpretation, text analysis, possible re-categorization, and, finally, the development of clusters, which were translated into themes in terms of health (Cilliers and Flotman 2016). Intersubjective evaluation processes within the team were used to develop categories and codes over the 3-year investigation period (Yin 2009).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Not only was the demands-resources model used among organisational workers to explain job characteristics and their relation to wellbeing, this model was also applied among university students [87][88][89]. It was revealed that students who encounter high study demands (e.g., study conditions that trigger stress reactions) and feel that they lack study resources eventually will become exhausted and cynical, and in turn experience negative psychological well-being [88].…”
Section: Predictors Of Well-beingmentioning
confidence: 99%
“…Similarly, Cilliers and Flotman [89] emphasised that postgraduate students who experience distress produced by job/study demands (e.g., role demands, being responsible for others, interpersonal demands) have feelings of languishing and being overwhelmed. Meanwhile, those who experience eustress caused by job/study resources (e.g., support from lecturers, interpersonal relationships) also eventually experience a feeling of flourishing (high selfefficacy, locus of control, and optimism).…”
Section: Predictors Of Well-beingmentioning
confidence: 99%